Pengaruh Citra Merek dan Kualitas Produk terhadap Keputusan Pembelian MS Glow di Solo - Hasna Asih Namiroh; Mirzam Arqy Ahmadi (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
The objective of this research is to evaluate the impact of brand image and product quality on consumer purchasing decisions regarding MS Glow products in Solo. A positive brand image can enhance consumers' trust in a particular brand; however, product quality remains the primary determinant of satisfaction and choice among consumers. Using qualitative methodology with phenomenological approach, the study aims to understand consumers’ experiences and perspectives towards MS Glow products. The findings indicate that strong brand images, such as reliable reputation and consumer confidence, significantly influence purchase decisions. Additionally, product qualities including durability, performance, design, and innovative features play crucial roles in consumer decision-making processes. This research is expected to help companies develop better marketing strategies to meet individual customer needs effectively.